Start Right ? A Biomechanical Review of Dive Start Performance - Lyttle, A.; Benjamvatra, N. (coachesinfo.com)
Swimming starts have come a long way since the `bottom first` entry used in the 17th century. In current competitive swimming, the dive start is a critical component of swimming performance. This is especially true for the shorter distances where the start has been estimated to contribute up to 30% of the total race in the 50m sprints (Fig. 1). Numerous examples can be cited to highlight the importance of starts. In the men`s 50 m freestyle final in the Sydney Olympic Games, there was only 0.05s separating 1st and 3rd places and in the same event at the 2003 World Championships, 0.52s separated 1st and 8th place. At the 1996 Olympics, Scott Miller lost the 100m butterfly final to Dennis Pankratov by 0.28s although he was already 0.40s behind at the initial 15m mark. Therefore, a small improvement in starting performance can potentially lead to substantial improvements in the event placing. Despite the importance, it is still common for swimmers and coaches to select their starting technique using a `follow the leader` approach, by mimicking the technique used by successful swimmers, rather than using objective information.